Zur Vollendung der »Religion in Geschichte und Gegenwart« und der »Theologischen Realenzyklopädie«. Zur Vollendung der »Religion in Geschichte und Gegenwart« und der »Theologischen Realenzyklopädie« - Smend, Rudolf (Zeitschrift für Theologie und Kirche, 2006)
To celebrate the completion of both works, the publishing companies organized a »Night of the Encyclopedia«, during which this lecture was given. It acknowledges the 4th edition of the RGG against the backdrop of the first three editions and the TRE against the backdrop of the Herzog-Hauck »Realencyclopädie« as documents of the history of theology in the 20th century.